Pemanfaatan Sistem Informasi Manajemen dalam Meningkatkan Efisiensi Operasional UMKM: Studi Kualitatif di Kantin Universitas Pamulang Viktor - Muhammad Najhan Tsaani; Ahmad Nursodiq; Dwi Fitria Alfiani; Najwa Masayu Azzahra; Muhamad Ario Isnandar; Pascal Ismail (Jurnal Publikasi Teknik Informatika, 2026)
This study investigates the effectiveness of Management Information System (MIS) implementation in enhancing operational efficiency among Micro, Small, and Medium Enterprises (MSMEs) at Kantin Universitas Pamulang Viktor. Employing a qualitative approach with descriptive analysis, this research collected primary data from 50 MSME respondents through structured interviews and observation. The findings reveal that 58% of MSMEs have adopted various forms of MIS, including Digital POS systems (34.5%), accounting applications (24.1%), spreadsheet tools (24.1%), and QRIS payment systems (17.2%). Quantitative analysis demonstrates that MSMEs utilizing MIS achieved significantly higher daily revenue (Rp1,047,931) compared to non-adopters (Rp784,762), representing a 33.5% increase. Furthermore, MIS-adopting businesses recorded higher daily customer counts (42.3 customers) versus non-adopters (29.8 customers), indicating improved service efficiency. The study identifies key benefits including streamlined transaction processing, accurate financial recording, and enhanced customer service quality. However, challenges such as limited digital literacy, initial investment costs, and technological adaptation remain significant barriers. This research contributes to the understanding of digital transformation in traditional food service MSMEs and provides practical recommendations for policy makers and MSME practitioners in accelerating digital adoption within campus-based economic ecosystems.